Early oxidation stages of the strained Ge/Si(105) surface: A reflectance anisotropy spectroscopy study. Issue 1 (28th April 2014) - Goletti, Claudio; Fazi, Laura; Hogan, Conor; Persichetti, Luca; Sgarlata, Anna; Palummo, Maurizia; Balzarotti, Adalberto
<x xml:space="preserve">Abstract</x> We have applied reflectance anisotropy spectroscopy (RAS) to investigate the rebonded‐step (RS) reconstructed strained Ge/Si(105) surface. RAS spectra display a marked peak at 2.1 eV that is completely cancelled after exposure to about 1200 L of molecular oxygen. Ab initio calculations of the RAS signal explain the experimental spectra in terms of optical transitions between filled bulk‐like states and empty surface bands. The early stages of exposure of the clean surface to molecular oxygen have been monitored by RAS and scanning tunneling microscopy (STM), correlating the evolution of the optical anisotropy to the bonding configuration of the adsorbed gas. Oxygen atoms are proposed to first adsorb onto the arms and later on the head dimers of the "horseshoe" motifs that comprise the RS reconstruction, thus gradually destroying the local order.